Molecular genetics of blood-fleshed peach reveals activation of anthocyanin biosynthesis by NAC transcription factors - Hui Zhou; Kui Lin‐Wang; Huiliang Wang; Chao Gu; Andrew P. Dare; Richard V. Espley; Huaping He; Andrew C. Allan; Yuepeng Han (2015)
Anthocyanin pigmentation is an important consumer trait in peach (Prunus persica). In this study, the genetic basis of the blood-flesh trait was investigated using the cultivar Dahongpao, which shows high levels of cyanidin-3-glucoside in the mesocarp. Elevation of anthocyanin levels in the flesh was correlated with the expression of an R2R3 MYB transcription factor, PpMYB10.1. However, PpMYB10.1 did not co-segregate with the blood-flesh trait. The blood-flesh trait was mapped to a 200-kb interval on peach linkage group (LG) 5. Within this interval, a gene encoding a NAC domain transcription factor (TF) was found to be highly up-regulated in blood-fleshed peaches when compared with non-red-fleshed peaches. This NAC TF, designated blood (BL), acts as a heterodimer with PpNAC1 which shows high levels of expression in fruit at late developmental stages. We show that the heterodimer of BL and PpNAC1 can activate the transcription of PpMYB10.1, resulting in anthocyanin pigmentation in tobacco. Furthermore, silencing the BL gene reduces anthocyanin pigmentation in blood-fleshed peaches. The transactivation activity of the BL-PpNAC1 heterodimer is repressed by a SQUAMOSA promoter-binding protein-like TF, PpSPL1. Low levels of PpMYB10.1 expression in fruit at early developmental stages is probably attributable to lower levels of expression of PpNAC1 plus the presence of high levels of repressors such as PpSPL1. We present a mechanism whereby BL is the key gene for the blood-flesh trait in peach via its activation of PpMYB10.1 in maturing fruit. Partner TFs such as basic helix-loop-helix proteins and NAC1 are required, as is the removal of transcriptional repressors.